2020
DOI: 10.5123/s1679-49742020000200005
|View full text |Cite
|
Sign up to set email alerts
|

Escorpionismo no Extremo Sul da Bahia, 2010-2017: perfil dos casos e fatores associados à gravidade*

Abstract: Objective: to describe the epidemiological profile of scorpionism and to investigate factors associated with case severity in the Far South of Bahia, Brazil. Methods: this was a descriptive study using data on scorpion accidents reported on the Notifiable Health Conditions Information System (SINAN) from 2010 to 2017; odds ratios (OR) were calculated to investigate factors associated with severe cases. Results: 3,055 cases were reported, of which 411 (13.5%) were severe and included 10 deaths; highest incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
2
9
0
5
Order By: Relevance
“…Envenomation was more prevalent in men than in women (59.8% vs. 40.2%), which was also reported by Lisboa and Bucaretchi 13,25 , while a higher incidence in women was observed by Carmo (54.9% vs. 45.1%) and Taniele-Silva (61.8% vs. 38.2%) 10,11 . Observing the mapping of the residential areas most prone to the occurrence of scorpions, it is clear that all inhabitants of a residence are equally susceptible to stings by scorpions, which is in accordance with our findings, considering that the differences in susceptibility between men and women are not statistically significant 1 .…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Envenomation was more prevalent in men than in women (59.8% vs. 40.2%), which was also reported by Lisboa and Bucaretchi 13,25 , while a higher incidence in women was observed by Carmo (54.9% vs. 45.1%) and Taniele-Silva (61.8% vs. 38.2%) 10,11 . Observing the mapping of the residential areas most prone to the occurrence of scorpions, it is clear that all inhabitants of a residence are equally susceptible to stings by scorpions, which is in accordance with our findings, considering that the differences in susceptibility between men and women are not statistically significant 1 .…”
Section: Discussionsupporting
confidence: 70%
“…The majority of the cases were mild (94.6%), with 4.5% of the cases being moderate and 0.9% severe. Other studies have also reported a higher incidence of mild cases in several regions of Brazil, while severe cases varied from 0.4% to 13.5% [10][11][12][13] . Envenoming with T. serrulatus registered in Santa Catarina did not evolve severely, which can be associated with the lower number of cases with children in this state, since other states show a higher prevalence in children aged 0-12 years old [10][11][12][13][14][15][16] and T. serrulatus is involved in most severe cases and fatal outcomes, especially when the victims are children 17 .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations